The personnel management system of the organization in the conditions of martial law and the main directions of its improvement - Anastasiia Radchenko; Oleksii Dzhusov (Challenges and Issues of Modern Science)
During periods of martial law, organizations encounter distinct challenges in sustaining effective personnel management systems. The enforcement of martial law frequently disrupts standard operations, creating significant obstacles for workforce management and organizational stability. The sudden imposition of new regulations and the heightened state of alert can lead to confusion, uncertainty, and increased stress among employees. This environment makes it difficult to maintain normalcy and efficiency in daily operations. Therefore, understanding and enhancing the personnel management system becomes crucial to ensure continuity and resilience in such demanding circumstances. This study explores the complex dynamics of personnel management within organizations functioning under martial law. By analyzing current systems and practices, it aims to illuminate the specific challenges faced by organizations during these times of increased security and instability. The research will delve into how martial law impacts various aspects of personnel management, such as recruitment, retention, training, and employee morale. Furthermore, it will examine the legal and ethical considerations that arise when managing personnel under martial law, including compliance with emergency regulations and the protection of employee rights. Additionally, this research seeks to pinpoint critical areas for improvement within the personnel management framework, providing insights into strategies and interventions that can bolster organizational resilience and effectiveness. For instance, it will investigate the role of leadership in navigating crises, the importance of clear communication channels, and the need for flexible and adaptive management practices. The study will also consider the psychological support required for employees who may be dealing with increased levels of stress and anxiety due to the uncertain and potentially dangerous environment.